A Study on Radio Access Technology Selection Algorithms - Wu, Leijia; Sandrasegaran, Kumbesan; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book discusses the basic idea of Common Radio Resource Management (CRRM), especially on the Radio Access Technologies selection part of CRRM. It introduces two interaction functions (information reporting function and RRM decision support function) and four interaction degrees (from low to very high) of CRRM. Four possible CRRM topologies (CRRM server, integrated CRRM, Hierarchical CRRM, and CRRM in user terminals) are described. The book presents different Radio Access Technologies selection algorithms, including single criterion and multiple criteria based algorithms are presented and compares them. Finally, the book analyses the advantages and disadvantages of the different selection algorithms.
Common Radio Resource Management -- Single Criterion Based Algorithms -- Load Balancing Based Algorithms -- Multiple criteria based algorithms.
Keywords: Engineering; Information storage and retrieval; Electrical engineering; Engineering; Communications Engineering, Networks; Information Storage and Retrieval; Signal, Image and Speech Processing; Electronic books